Intercalated Disk Extracellular Nanodomain Expansion in Patients With Atrial Fibrillation - Raisch, Tristan B.; Yanoff, Matthew S.; Larsen, Timothy R.; Farooqui, Mohammed A.; King, D. Ryan; Veeraraghavan, Rengasayee; Gourdie, Robert G.; Baker, Joseph W.; Arnold, William S.; AlMahameed, Soufian T.; Poelzing, Steven (Frontiers in Physiology, 2018)
Aims: Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous evidence in animal models suggests that the gap junction (GJ) adjacent nanodomain – perinexus – is a site capable of independent intercellular communication via ephaptic transmission. Perinexal expansion is associated with slowed conduction and increased ventricular arrhythmias in animal models, but has not been studied in human tissue. The purpose of this study was to characterize the perinexus in humans and determine if perinexal expansion associates with AF. Methods: Atrial appendages from 39 patients (pts) undergoing cardiac surgery were fixed for immunofluorescence and transmission electron microscopy (TEM). Intercalated disc distribution of the cardiac sodium channel Nav1.5, its 1 subunit, and connexin43 (Cx43) was determined by confocal immunofluorescence. Perinexal width (Wp) from TEM was manually segmented by two blinded observers using ImageJ software. Results: Nav1.5, 1, and Cx43 are co-adjacent within intercalated discs of human atria, consistent with perinexal protein distributions in ventricular tissue of other species. TEM revealed that the GJ adjacent intermembrane separation in an individual perinexus does not change at distances greater than 30nm from the GJ edge. Importantly, Wp is significantly wider in patients with a history of AF than in patients with no history of AF by approximately 3nm, and Wp correlates with age (R=0.7, p<0.05). Conclusions: Human atrial myocytes have voltage-gated sodium channels in a dynamic intercellular cleft adjacent to gap junctions that is consistent with previous descriptions of the perinexus. Further, perinexal width is greater in patients with AF undergoing cardiac surgery than in those without.